Penggunaan Model Pembelajaran Discovery Learning dalam Meningkatan Hasil Belajar Siswa Sekolah Dasar - Connyta Elvadola; Yulita Dwi Lestari; Try Indiastuti Kurniasih (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2022)
Currently, education is required to be better related to student learning outcomes. Learning outcomes are strongly influenced by how the teacher chooses the delivery model of learning material in the classroom. Therefore, this article was created with the aim of providing references related to learning models which in their application have been proven to improve student learning outcomes in elementary schools. In Indonesia, there are various types of learning models, each of which has its own advantages and disadvantages. On this occasion the researcher only chose one learning model, namely discovery learning. So the researchers conducted research using the meta-analysis method, which is an effort to summarize various research results by studying 5 data documents related to the use of published discovery learning models. From the research conducted, it is proven that the discovery learning model is able to help increase student activity in the learning process with students finding their own information so that it shows an increase in student learning outcomes both in elementary school.